(9b+8)(9b-8)=

Simple and best practice solution for (9b+8)(9b-8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9b+8)(9b-8)= equation:


Simplifying
(9b + 8)(9b + -8) = 0

Reorder the terms:
(8 + 9b)(9b + -8) = 0

Reorder the terms:
(8 + 9b)(-8 + 9b) = 0

Multiply (8 + 9b) * (-8 + 9b)
(8(-8 + 9b) + 9b * (-8 + 9b)) = 0
((-8 * 8 + 9b * 8) + 9b * (-8 + 9b)) = 0
((-64 + 72b) + 9b * (-8 + 9b)) = 0
(-64 + 72b + (-8 * 9b + 9b * 9b)) = 0
(-64 + 72b + (-72b + 81b2)) = 0

Combine like terms: 72b + -72b = 0
(-64 + 0 + 81b2) = 0
(-64 + 81b2) = 0

Solving
-64 + 81b2 = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '64' to each side of the equation.
-64 + 64 + 81b2 = 0 + 64

Combine like terms: -64 + 64 = 0
0 + 81b2 = 0 + 64
81b2 = 0 + 64

Combine like terms: 0 + 64 = 64
81b2 = 64

Divide each side by '81'.
b2 = 0.7901234568

Simplifying
b2 = 0.7901234568

Take the square root of each side:
b = {-0.888888889, 0.888888889}

See similar equations:

| 6x+10y=-10 | | 809+x=1268 | | 5x-8/3-4x=6x | | 4(2x+6+7)-5x=61 | | 2x^2+8n=-6 | | 4s+14=30 | | 7+15t=-38 | | 8ax-5(ax+b)=6b+3x | | 22x+6x-14=22x+10-6x | | 22x+6x-14=22x+10-6 | | 2-10n+5n=6-89 | | 2x+4(1-x)=3 | | 9t+3=28.2 | | 9222222222222222xa= | | 69=-31+x | | 8y^2+16y=0 | | −70x^2/28x | | 91=-w+189 | | ax+2x=c | | 225=9(7+9+y) | | 6-6(4m-6)=114 | | f(x)=3(A) | | 8a^4-3ab^2c=0 | | (X+3)(x+2)=72 | | 28x+5y=2y+28 | | -10ln[(93.7-76.5)/(98.6-76.5)] | | (x+6)x=216 | | (7h+2)(7h-2)= | | 4(1.75y)=7y | | (x+6)=216 | | Y/3-6=3-2/3y | | 4x+7x+10x=189 |

Equations solver categories